Campylobacter jejuni gene cj0511 encodes a serine peptidase essential for colonisation - Karlyshev, A.V.; Thacker, G.; Jones, M.A.; Clements, M.O.; Wren, Brendan W. (Elsevier, 2014)
According to MEROPS peptidase database, Campylobacter species encode 64 predicted peptidases. However, proteolytic properties of only a few of these proteins have been confirmed experimentally. In this study we identified and characterised a Campylobacter jejuni gene cj0511 encoding a novel peptidase. The proteolytic activity associated with this enzyme was demonstrated in cell lysates. Moreover, enzymatic studies conducted with a purified protein confirmed a prediction of it being a serine peptidase. Furthermore, cj0511 mutant was found to be severely attenuated in chicken colonisation model, suggesting a role of the Cj0511 protein in infection.